Clinical outcomes of immune checkpoint inhibitor combined with other targeted or immunological therapy regimens for the treatment of advanced bile tract cancer: a systematic review and meta-analysis - Zhou, Jianpeng; Li, Jia; Fan, Zhongqi; Lv, Guoyue; Wang, Guangyi (Frontiers in Immunology, 2024)
Background and aims A single immune checkpoint inhibitor (ICI) regimen has limited value in treating advanced bile tract cancer (BTC); therefore, ICI combination therapy is often applied. This meta-analysis aimed to evaluate the effectiveness and safety of ICI combination therapy for advanced BTC. Methods The study protocol was registered on PROSPERO (CRD42023452422). Data on the median progression-free survival (PFS), median overall survival (OS), objective response rate (ORR), disease control rate (DCR), and grade ≥3 adverse events (AEs) reported in relevant studies were pooled and analyzed to determine the efficacy and safety of ICI combination therapy. Results In total, 15 studies with 665 patients were included in this meta-analysis. The overall ORR and DCR were 34.6% and 77.6%, respectively. The overall median PFS and OS were 6.06 months [95% confidence interval (CI): 4.91–7.21] and 12.11 months (95% CI: 10.66–13.55), respectively. Patients receiving ICI combination therapy in addition to other therapies had a considerably prolonged median PFS and OS (z=9.69, p<0.001 and z=16.17, p<0.001). Patients treated as first-line treatment had a substantially longer median PFS and OS compared to patients treated as non-first-line treatment (z=11.19, p<0.001 and z=49.17, p<0.001). The overall pooled grade ≥3 AEs rate was 38.2% (95% CI: 0.268–0.497) and was not influenced by whether ICI therapy was combined with other treatments or not or the treatment line. Conclusion Advanced BTC patients may benefit from ICI combination treatment without additional AEs. However, concurrent chemotherapy or radiotherapy is still needed to achieve better outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023452422.